Template-free synthesis of N-doped carbon with pillared-layered pores as bifunctional materials for supercapacitor and environmental applications - Tian, W.; Zhang, H.; Sun, Hongqi; Tade, Moses; Wang, Shaobin (Pergamon, 2017)
© 2017 Elsevier Ltd Cross-linked, N-doped, pillared-layered porous carbons (NCs) were prepared via a one-pot, template-free pyrolysis process at 600 (NC600), 700 (NC700) and 800 °C (NC800), which have bifunctional applications in supercapacitors and environmental remediation. NC700 displays a high surface area (2118 m 2  g −1 ) and a specific capacitance of 305 F g −1  at 0.2 A g −1 in a two-electrode setup. The maximum energy density of NC700 was 20.4 W h/kg at a power density of 139 W kg −1 and 89.1% capacitance was retained after 10000 cycles of charge-discharge at 5 A g −1 . For water remediation, NC800 displayed high adsorption capacities towards flame retardant tetrabromobisphenol A (TBBPA, 372  mg g −1 ) and antibiotic sulfachloropyridazine (SCP, 288 mg g −1 ) solutions, while NC700 showed the most efficient SCP oxidation removal. These results suggest low-cost and green carbon materials as electrodes in flexible energy storage devices, metal-free adsorbents as well as catalysts for high efficient removal of emerging contaminants in aqueous solution.